2012
DOI: 10.1161/circulationaha.112.144055
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Lipoprotein Cholesterol–Lowering Effects of AMG 145, a Monoclonal Antibody to Proprotein Convertase Subtilisin/Kexin Type 9 Serine Protease in Patients With Heterozygous Familial Hypercholesterolemia

Abstract: Background-Despite statin treatment, many patients with heterozygous familial hypercholesterolemia do not reach desired low-density lipoprotein cholesterol (LDL-C) targets. AMG 145, a fully human monoclonal antibody against proprotein convertase subtilisin/kexin type 9 (PCSK9) serine protease, demonstrated significant reductions in LDL-C in phase 1 studies. This phase 2, multicenter, double-blind, randomized, placebo-controlled, dose-ranging study evaluated the efficacy and safety of AMG 145 in heterozygous fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
294
0
8

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 472 publications
(316 citation statements)
references
References 24 publications
14
294
0
8
Order By: Relevance
“…A total of 138 study arms from 35 studies were analyzed, comprising 45 539 patients (Table S1). 5, 11, 12, 13, 14, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43 Alirocumab was used in 18 studies (28 treatment arms), and evolocumab was used in 17 studies (39 treatment arms; Figure 1); placebo was the most common control used (52 control arms), with ezetimibe used in 17 arms, and standard therapy in 2 arms. Eight studies were of an exclusively FH population, and 5 studies included only patients intolerant to statins.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 138 study arms from 35 studies were analyzed, comprising 45 539 patients (Table S1). 5, 11, 12, 13, 14, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43 Alirocumab was used in 18 studies (28 treatment arms), and evolocumab was used in 17 studies (39 treatment arms; Figure 1); placebo was the most common control used (52 control arms), with ezetimibe used in 17 arms, and standard therapy in 2 arms. Eight studies were of an exclusively FH population, and 5 studies included only patients intolerant to statins.…”
Section: Resultsmentioning
confidence: 99%
“…The RUTHERFORD study (33) showed more reduction of TC in comparison to other studies. The included patients were HeFH with statin therapy.…”
Section: Discussionmentioning
confidence: 55%
“…The summary for the standardized effect size of mean differences of % change from baseline at the end of the study for the Ratio of TC to HDL-C in FH patients "∆Ratio of TC to HDL-C" for evolocumab therapy for seven included studies comparing to placebo (29)(30)(31)(32)(33)(34)36) was -39.14 with 95% CI= -43.34 to -34.95 (P< 0.0001, Figure 4a). The Cochrane Q test for heterogeneity indicated that the studies are heterogeneous (P= 0.0002), I² (inconsistency) of 77% with 95% CI= 41% to 87.4% and could not be combined, thus the random effects for individual and summary of effect size for standardized mean differences was applied.…”
Section: Ratio Of Tc To Hdl-c Effect Of Evolocumab In Comparison To Pmentioning
confidence: 99%
“…These patients include those with an inadequate response to high potency statins or those intolerant to statin therapy either at any dose, or at a higher dose, required for adequate LDL-C lowering. Based on early clinical reports, PCSK9 monoclonal antibodies appear generally safe and capable of addressing important limitations of contemporary lipidlowering therapy [4,[6][7][8][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%